HER2/neu Testing in Gastric Cancer by Immunohistochemistry: Assessment of Interlaboratory Variation - Sheffield, Brandon S.; Garratt, John; Kalloger, Steve E.; Li-Chang, Hector H.; Torlakovic, Emina E.; Gilks, C. Blake; Schaeffer, David F. (Archives of pathology & laboratory medicine (1976), 2014)
Immunohistochemical (IHC) testing for HER2/neu is becoming the standard of care for guiding adjuvant treatment of gastric carcinoma with trastuzumab. To assess interlaboratory variation in IHC staining and interpretation across multiple laboratories. A tissue microarray consisting of 45 cores from 28 gastric cancers was distributed to 37 laboratories for HER2/neu assessment. The IHC results were compared against expert scores at an academic institution and correlated with in situ hybridization results from the originating specimen. Interlaboratory agreement was calculated using Cohen κ statistic. The survey demonstrated several variations in IHC methods, including the primary antibodies in use. There was excellent agreement among laboratories in HER2/neu(+) (IHC 3(+)) cases (κ = 0.80 ± 0.01) and very good agreement among laboratories in HER2/neu(-) (IHC 0 or 1(+)) cases (κ = 0.58 ± 0.01). Less agreement was observed among laboratories when scoring equivocal (IHC 2(+)) cases (κ = 0.22 ± 0.01). Sensitivity and specificity of HER2/neu IHC were 99% and 100%, respectively, when measured against expert review and consensus score as a reference standard. There is substantial interlaboratory agreement in the interpretation of HER2/neu IHC despite variability in protocols. Although HER2/neu IHC is a highly sensitive and specific test, primary antibody selection may significantly affect IHC results. Furthermore, gastric tumors require a unique scoring system and expertise in interpretation. Intratumoral heterogeneity has a significant effect on HER2/neu scoring by IHC. Ongoing quality assurance exercises among laboratories will help ensure optimized HER2/neu testing.